Blogging as a Tool for Real-Time Learning in Medical Microbiology - Lloyd, Charmaine (Frontiers in Microbiology, 2021)
Learning Medical Microbiology (MMB) at the undergraduate level is challenging as the subject is content-heavy. While foundations are important in theory and practicals, here, I explore blogging as a complementary real-time learning tool to deliver beyond-the-classroom learning opportunities and have a sustainable online learning strategy for disruptive situations. The approach involved instructing students to choose one infectious disease topic, for which traditional and non-traditional scientific articles could be found in the preceding and current month(s). They were to document new information on the topic, as it became available, from the following (but not limited to) resources - news sites, journals, CDC, WHO, vaccine, drug trial sites. At the end of the term, students presented their work in a Blog show-off session. Grades were assigned for the frequency of posts, articulation and non-plagiarism among other criteria. Blog-based learning was found to be an engaging tool that satisfied all criteria under Bloom’s taxonomy. Students developed a continued intrigue for the topic and appreciated the diverse fields in which MMB knowledge could be applied within and outside academia. In view of these benefits, I suggest the use of blogs for an immersive, broad learning experience.